Evaluation of the effectiveness of 6-week vitamin D treatment in children aged 5 to 15 years with vitamin D insufficiency - Saneifard, Hedyeh; karbasian, Fereshteh; Farsi, Yeganeh; Rafiee Taghanaki, Sahar (Student Research in Translational Medicine, 2021)
Background: Vitamin D insufficiency is a common disorder worldwide and children are involved in this disorder. In this study, we aimed to evaluate the effectiveness of vitamin D insufficiency treatment with vitamin D 50,000 IU in children who had vitamin D insufficiency. Methods: Children’s vitamin D levels were evaluated and if they had vitamin D insufficiency, one pearl of vitamin D 50,000 IU was prescribed weekly for 6 weeks, and after 6 weeks, vitamin D levels were checked again. Then all data were analyzed by SPSS software version 20. Results: In this study, 97 children were evaluated and 61.9% were boys. The average age of children was 101.01 ± 19.27 months. The average BMI of these children was 15.46 ± 2.52 kg/m2. The initial vitamin D level was 18.21 ± 6.42 ng / mL with a range of 4.2 to 29.8. After treatment, this level reached 41.08 ± 14.61ng / mL (12.2 - 98.4 ng / mL) and this increase was statistically significant (P-value< 0.005). There was no correlation between age, gender, height, and BMI with the increased efficacy of vitamin D level with one pearl of vitamin D 50000 unit. Conclusion: Using one pearl of vitamin D 50000 IU weekly for 6 weeks is a good method for vitamin D insufficiency treatment in children.